Analysis of torque ripple and fault-tolerant capability for a 16/10 segmented switched reluctance motor in HEV applications. Issue 6 (23rd August 2019) - Sun, Xiaodong; Wu, Jiangling; Wang, Shaohua; Diao, Kaikai; Yang, Zebin
Abstract : Purpose: The torque ripple and fault-tolerant capability are the two main problems for the switched reluctance motors (SRMs) in applications. The purpose of this paper, therefore, is to propose a novel 16/10 segmented SRM (SSRM) to reduce the torque ripple and improve the fault-tolerant capability in this work. Design/methodology/approach: The stator of the proposed SSRM is composed of exciting and auxiliary stator poles, while the rotor consists of a series of discrete segments. The fault-tolerant and torque ripple characteristics of the proposed SSRM are studied by the finite element analysis (FEA) method. Meanwhile, the characteristics of the SSRM are compared with those of a conventional SRM with 8/6 stator/rotor poles. Finally, FEA and experimental results are provided to validate the static and dynamic characteristics of the proposed SSRM. Findings: It is found that the proposed novel 16/10 SSRM for the application in the belt-driven starter generator (BSG) possesses these functions: less mutual inductance and high fault-tolerant capability. It is also found that the proposed SSRM provides lower torque ripple and higher output torque. Finally, the experimental results validate that the proposed SSRM runs with lower torque ripple, better output torque and fault-tolerant characteristics, making it an ideal candidate for the BSG and similar systems. Originality/value: This paper presents the analysis of torque ripple and fault-tolerant capability for a 16/10 segmented switched reluctance motor in hybrid electric vehicles. Using FEA simulation and building a test bench to verify the proposed SSRM's superiority in both torque ripple and fault-tolerant capability.